P‐140: Evaluate and Improve Color Washout and Color Shift of VA LCD. Issue 1 (25th September 2020) - Chen, Chun-Chi; Wang, Yan-Xue; Lin, Yue-Cu; Zheng, Wei-Wei; Yu, Gang; Chiu, Chung-Yi; Zhao, Bin; Zhang, Xin
Abstract : There are color washout and color shift in VA LCD when we see the LCD with a view angle, so we make the different voltage between main and sub pixel to create 8 domain to improve the color washout issue, but there is color shift need to be improved if we just only reduce the delta voltage between main and sub pixel. Because human eye is very sensitive about skin color, it is important to improve color shift of skin color. This paper we established a simulation system to evaluate the color washout and color shift of skin color, then we can optimize design for improving the issue. We created a new circuit, and we can use it to fine tune different delta voltage(between sub and main pixel) between R/G/B pixel for improve color shift of skin color. Final we succeeded to establish a system to evaluate color shift of skin color in VA LCD, and improved by fine tuning delta voltage by new circuit.